2009
DOI: 10.1016/j.ejcts.2008.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in children: native valve preservation is frequently possible despite advanced clinical disease

Abstract: Children undergoing surgery for infective endocarditis frequently have advanced disease with embolic complications and double valve involvement. However, preservation of the native valve is frequently possible. Need for valve replacement is suggested by leaflet thickening and embolization. Despite the advanced pathology, survival and functional outcomes are favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
8

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 17 publications
0
26
1
8
Order By: Relevance
“…24,110,111 This may be attributable in part to the proliferation of intravascular catheters, as well as the nonspecificity of the Duke criteria in children causing false-positive diagnoses. Almost all staphylococci are highly resistant to penicillin G and ampicillin.…”
Section: Staphylococcal Endocarditis On Native Valves or Prosthetic Mmentioning
confidence: 99%
See 2 more Smart Citations
“…24,110,111 This may be attributable in part to the proliferation of intravascular catheters, as well as the nonspecificity of the Duke criteria in children causing false-positive diagnoses. Almost all staphylococci are highly resistant to penicillin G and ampicillin.…”
Section: Staphylococcal Endocarditis On Native Valves or Prosthetic Mmentioning
confidence: 99%
“…159,160 Depending on the degree of valve or great vessel root damage, valvesparing operations are often possible. 110,152,161 In some circumstances, cardiological evaluation may suggest a need for early surgical therapy, performed even before sterilization of blood. In a recent 15-year review of children treated for IE at the Texas Heart Institute in Houston, TX, early surgery was performed in 61% of patients, with most of these surgeries occurring within 7 days and half within 3 days of diagnosis.…”
Section: Indications For Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Hickey et al (6) have indicated that native valve preservation should be preferred in the children with IE. Though valve replacement confers to a high risk of repeat replacement at the 15 th year (7), valve replacement is necessary in many Chinese children with IE because either they come to hospital with advanced clinical manifestations or their valves are damaged too severely where preservation of the values is not a feasible option.…”
Section: Original Articlementioning
confidence: 99%
“…2,12 Infective endocarditis can occur in children without previously cardiac defects in 20% cases. 13,14 Rightsided IE rarely occurs with 5-10% incidence from all cases, especially in HIV or immunosuppresed patients. Infections related with low sterility of intravenous (IV) injection, contaminated IV drugs, and immunity abnormalities.…”
mentioning
confidence: 99%